Analysis Of The Hashtag #Samasamabelajar Public Relations Campaign (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The purpose of this study was to analyze the effectiveness of the #samasamasiswa public relations campaign on TikTok in the period 21 December 2021-2 January 2022. Using a positivistic paradigm, descriptive quantitative research was conducted by collecting data using tech algorithm software. Furthermore, the researcher deepened the data analysis by relating the 10 step PR campaign theory from Anne Gregory and the innovation diffusion theory. The results of the big data algorithm analysis show that after the #samasamasiswa campaign, the community produced a total of 975 videos. The government works closely with TikTok through a continuing education campaign, the creation of Tiktokclass and University Class Week. The government provides space for the public to play an active role in producing educational social media content in order to provide a positive image of the government. In addition, TikTok social media is a means of delivering government information to the public. The research findings show that the top viewers are not from the official tiktok official video content. Documentation of known content only uses #samasamabelar and does not use the hashtag #merdekasiswa so that it is not in accordance with the campaign provisions. Future research can focus on audience studies related to educational content hashtags, further research can research other niches on TikTok.